Regeneration Capacity of Indica Rice cv. Bengawan Solo in Two Types of Regeneration Media through Microprojectile Bombardment - TRI JOKO SANTOSO; SUDARSONO SUDARSONO; HAJRIAL ASWIDINNOOR; IDA HANARIDA SOMANTRI (Bogor Agricultural University, Indonesia, 2005)
Factors affecting the success of gene delivery into cells/tissues of rice mediated by particle bombardment have been investigated. However, their effects on regeneration capacity of rice explants have not been investigated. Objectives of this experiments were to evaluate the effects of particle bombardment on regeneration capacity of indica rice cv. Bengawan Solo calli and the effects of four regeneration media on the development of bombardment calli. Calli of indica rice were initiated from mature seeds on callus-inducing medium. They were transferred on osmoticum containing medium prior to bombardment and maintained on the medium up to two days. Particle bombardment was conducted at 16 cm bombardment distance, 27 cm Hg helium pressure and using standard procedures for preparation of microprojectile particles. The bombarded calli were cultured on RNB or RMS regeneration medium, with or without spermidine addition. Results of the experiment indicated particle bombardment affected the survival of explants of indica rice but did not affect the development of the explants. The development of explants was rather dependent on the regeneration media than on the particle bombardment treatment. RMS medium was better than RNB medium for shoots inducing from bombarded indica rice explants.